2014
DOI: 10.1098/rsbl.2013.1096
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term effects of litter size manipulation in a small wild-derived rodent

Abstract: Iteroparous organisms maximize their overall fitness by optimizing their reproductive effort over multiple reproductive events. Hence, changes in reproductive effort are expected to have both short-and long-term consequences on parents and their offspring. In laboratory rodents, manipulation of reproductive efforts during lactation has however revealed few shortterm reproductive adjustments, suggesting that female laboratory rodents express maximal rather than optimal levels of reproductive investment as obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…This contrasts with several previous studies which have suggested that increased nursing costs of larger litters only affect the success of current reproduction (Hare and Murie, 1992;Kenagy et al, 1990;Mappes et al, 1995;Neuhaus, 2000;Oksanen et al, 2001). Instead, the results of the present study are consistent with those of other studies showing a trade-off (Koivula et al, 2003;Lehto Hurlimann et al, 2014) The immediate cost of experimentally elevated litter size was the small size of pups at the time of weaning. For M. musculus, the suggested minimal physiological weaning mass, at which pups reach a state of independence and are able to survive on their own, is around 9 g (König and Markl, 1987).…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…This contrasts with several previous studies which have suggested that increased nursing costs of larger litters only affect the success of current reproduction (Hare and Murie, 1992;Kenagy et al, 1990;Mappes et al, 1995;Neuhaus, 2000;Oksanen et al, 2001). Instead, the results of the present study are consistent with those of other studies showing a trade-off (Koivula et al, 2003;Lehto Hurlimann et al, 2014) The immediate cost of experimentally elevated litter size was the small size of pups at the time of weaning. For M. musculus, the suggested minimal physiological weaning mass, at which pups reach a state of independence and are able to survive on their own, is around 9 g (König and Markl, 1987).…”
Section: Discussioncontrasting
confidence: 77%
“…litter size at weaning was 276% larger but total litter mass was only 38% greater, resulting in significantly smaller pups in enlarged litters than in reduced ones. Other studies in rodents have shown similar effects of enlarged litters (Lehto Hurlimann et al, 2014;Mappes et al, 1995;Oksanen et al, 2001;Rogowitz, 1998;Speakman et al, 2001). For instance, in common voles, Microtis arvalis, females with an enlarged litter showed increased reproductive effort (i.e.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…food abundance (Glazier, 2009d). Experimentally enlarged litter sizes result in increased BMR in lactating females of the common vole Microtus arvalis (Pallas) (Hürlimann et al, 2014), thus showing that increased reproductive energy demand can stimulate metabolic rate, rather than vice versa as expected by the metabolic pacemaker assumption. Experimentally enlarged litter sizes result in increased BMR in lactating females of the common vole Microtus arvalis (Pallas) (Hürlimann et al, 2014), thus showing that increased reproductive energy demand can stimulate metabolic rate, rather than vice versa as expected by the metabolic pacemaker assumption.…”
Section: (3) Reproductive Ratementioning
confidence: 92%
“…Central to life‐history theory, the “cost of reproduction” hypothesis predicts that breeding individuals should trade‐off high investments into current reproduction with future survival or reproductive prospects (Hirshfield & Tinkle, ; Reznick ; Stearns, ; Williams, ). While fitness costs to reproduction have often been highlighted (Descamps, Boutin, McAdam, Berteaux, & Gaillard, ; Flatt, ; Koivula, Koskela, Mappes, & Oksanen, ; Lehto Hurlimann, Stier, Scholly, Criscuolo, & Bize, ; Linden & Møller, ; Nager, Monaghan, & Houston, ; Nur, ; Penn & Smith, ), the mechanisms responsible for such costs remain poorly understood, despite an increasing effort to integrate physiological approaches in understanding this compromise (Rubach et al, ; Zera & Harshman, ).…”
Section: Introductionmentioning
confidence: 99%